Pengembangan Media Pembelajaran E-Book Digital Berbasis Android Pada Mata Kuliah Instalasi Listrik - Ilham Novian Pratama; Irwanto Irwanto; Bagus Dwi Cahyno (PTE FTK UIN Ar-Raniry, 2022)
This study aims to produce a digital e-book learning media product with the assistance of an android smartphone as a learning resource in electrical installation courses. This study uses the type of Research and Development (R & D) type of Lee and Owen's theory development model including Analysis, Design, Development, Implementation, and Evaluation. Collecting data in this research used a questionnaire method and direct observation. The data collection technique which involved 20 respondents, 3 media experts, 3 material experts and 3 user experts. Based on the findings of the research analysis on the development of learning products with the help of Android Smartphones, it was found that the feasibility of learning media in terms of media experts with an average value of 83 is included in the